No Evidence for an Association of Vitamin D Deficiency and Migraine: A Systematic Review of the Literature. (8th May 2014) - Lippi, Giuseppe; Cervellin, Gianfranco; Mattiuzzi, Camilla
Abstract : Vitamin D deficiency is associated with a number of human disorders, including cardiovascular disease, cancer, diabetes, frailty, and infections. Since an association between vitamin D and migraine has also been recently speculated, we performed an electronic search on Medline, Scopus, and Web of Science using the keywords "migraine" and "vitamin D, " "25OH-D" "cholecalciferol, " "ergocalciferol, " with no language or date restriction. The electronic search allowed identifying seven studies (3 observational, 2 cross-sectional, and 2 case reports). The two case reports, including four women, showed favourable effects of vitamin D supplementation on migraine severity, but these studies were small and not placebo controlled. As regards the three observational studies, vitamin D deficiency was observed in 13.2 to 14.8% of migraine patients, and these rates do not differ from those reported in the general population (i.e., vitamin D deficiency between 22 and 42%). The results of the two cross-sectional studies are even more controversial, since no association was found between vitamin D status and migraine in both trials. In conclusion, the current evidence suggests that the association between migraine and vitamin D lacks reliable scientific support.